Os sentidos da medida socioeducativa de internação para adolescentes que possuem esta vivência - Oliveira, Natache Khrystie Costa de (2017)
To each infraction act reflected in the media, the discussion about the responsibility of the adolescent author of an infraction act reopens with intensity. Questions about the reduction of the penal age, duration, treatment and efficiency of the socio-educational measures, among them the one of deprivation of liberty, and other debates on the condition of the adolescent in taking responsibility for its actions arise; Revealing, in most cases, limited discussions about the responsibility of the social structure as part of the infractional involvement of adolescents. In view of this scenario, the objective of this study is to discuss about the socio-educational measure of deprivation of liberty, based on the senses given by the adolescent who has this experience and to understand the intervention that it produces in the one for whom it is thought - the adolescent. At the same time, we seek to reflect on the effectiveness of the interventions carried out in this context by the psychologist and other professionals who are actors of the Socio-educational Measure. The method used was of semi-directed interviews, analyzed through the reference of the Nucleus of Meanings. Participants were 04 adolescents at different times of said experience, considering that we do not know the best time to signify it. Therefore, we interviewed 02 adolescents in compliance with the hospitalization and 02 who left more than three years ago and are already disconnected from any Measure. The discussions were built based on the support provided by Socio-Historical Psychology as a theoretical reference, enabling a critical understanding of the social structure in which the exposed issues are embedded and the understanding of the human condition as capable of transforming and being transformed by the reality that experience